2016
DOI: 10.1038/srep25420
|View full text |Cite
|
Sign up to set email alerts
|

Mobility and Muscle Strength Together are More Strongly Correlated with Falls in Suburb-Dwelling Older Chinese

Abstract: Falls are common in older adults and result in adverse outcomes. Impaired mobility and poor muscle strength have been consistently identified as the main contributors to falls. We choose three easy-to-perform tests (i.e. Timed Up and Go test (TUGT), walking speed (WS) and grip strength (GS)) in order to assess mobility and muscle strength to further define their relationship with falls. This study is cross-sectional, consisting of 1092 residents over 60-year-old; 589 were female. 204 (18.68%) participants repo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 51 publications
2
23
2
Order By: Relevance
“…Previous studies have also reported differences between fallers and non-fallers in terms of handgrip strength [21][22][23]. Combined, these results do support the use of handgrip strength assessments as a simple screening tool in clinical practice, although its combination with other measures (e.g., functional mobility tests) could enhance predictive accuracy [34].…”
Section: Discussionsupporting
confidence: 55%
“…Previous studies have also reported differences between fallers and non-fallers in terms of handgrip strength [21][22][23]. Combined, these results do support the use of handgrip strength assessments as a simple screening tool in clinical practice, although its combination with other measures (e.g., functional mobility tests) could enhance predictive accuracy [34].…”
Section: Discussionsupporting
confidence: 55%
“…Deficits in muscular function are consistently reported in patients with knee OA and in patients who undergo knee arthroplasty 6 , 42 45 . Knee pain and quadriceps weakness affect the sensory and mechanical functions of the joint, and these factors are associated with increased postural sway 44 47 , which results in balance difficulties and increased risk of falls 48 , 49 .…”
Section: Discussionmentioning
confidence: 98%
“…Balance is a complex function that requires the integration of sensory information of the position of the body and the ability to make proper motor responses to body movement 3 . Balance is essential for maintaining postural stability while performing daily activities 4 , and loss of balance is a common cause of falls in older people 5 , 6 .…”
Section: Introductionmentioning
confidence: 99%
“…In particular, progress remains limited for the prediction whether an individual will sustain a hip fracture within the next 5 or 10 years. In contrast to vertebral fractures, almost all osteoporotic hip fractures are caused by a fall, which is associated with muscle strength [95] , [96] , [97] , [98] . Age-related loss of skeletal muscle mass is associated with the loss of bone mass [99] , [100] , and low muscle attenuation is associated with obesity and impaired muscle function [101] .…”
Section: Applications Of Quantitative Muscle Imaging By Ctmentioning
confidence: 99%